Modification of the Method for Determining Myeloperoxidase in Blood Neutrophils - R. Korablyeva , Tatyana; V. Senchuk, Ivan; E. Ageeva, Elizaveta (KnE Life Sciences, 2021)
Myeloperoxidase is a heme-containing peroxidase expressed primarily in neutrophils and to a lesser extent in monocytes. Determining the activity of myeloperoxidase in blood cells is one of the tests of the immune status of animals. Conventional methods are based on the oxidation of benzidine by the peroxide system to the unstable benzidine blue, which spontaneously turns into stable brown benzidine. The aim of this study was to develop a modification of the cytological determination of the myeloperoxidase enzyme using metol. The relative percentage of peroxidase-positive neutrophils in the peripheral blood of animals was determined after 100 neutrophils had been counted. The task was achieved by using the reaction with metol in the method of cytological determination of the activity of neutrophil myeloperoxidase in animal blood smears, which was based on the oxidation of metol by a peroxide system. Images of micropreparations were digitized using a Sony device for processing the received images of the cells. The Image Tool computer program was used for this purpose. The biological substrate was processed from a buffer-incubation mixture with subsequent drying and microscopy. The main new modification of the method was using metol. Metol does not have the ability to inhibit the activity of myeloperoxidase. The research showed easy and fast results. This method is economical and perspective for using in practice. Keywords: myeloperoxidase, blood, neutrophils, metol